2013
DOI: 10.1186/1477-7819-11-129
|View full text |Cite
|
Sign up to set email alerts
|

Unique clinicopathological features of metaplastic breast carcinoma compared with invasive ductal carcinoma and poor prognostic indicators

Abstract: BackgroundMetaplastic breast carcinoma is a rare aggressive malignant neoplasm. The purposes of this study are to review the pathologic features and clinical outcomes of metaplastic breast carcinoma compared to invasive ductal carcinoma and to evaluate the prognosis of metaplastic breast carcinoma.MethodsThe cases of 55 patients with metaplastic breast carcinomapresenting between 1991 and 2006 were analyzed and compared to the cases of 767 age-matched patients with invasive ductal carcinoma from the same time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
138
3
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 22 publications
14
138
3
9
Order By: Relevance
“…Core needle biopsy and aspiration cytology may aid in a pre-operative diagnosis, but the probability of misdiagnosis would increase in the presence of hemorrhage or necrosis due to inadequate sampling or a poor choice of puncture region (1). In the majority of cases, the transition foci between metaplastic carcinoma and invasive ductal carcinoma were only observed following surgical biopsy (1,3,9,11). Therefore, extensive sampling by surgical biopsy and immunohistochemical examination should be performed to avoid misdiagnosis.…”
Section: Pathological Type Of Carcinoma Sonography ------------------mentioning
confidence: 99%
See 4 more Smart Citations
“…Core needle biopsy and aspiration cytology may aid in a pre-operative diagnosis, but the probability of misdiagnosis would increase in the presence of hemorrhage or necrosis due to inadequate sampling or a poor choice of puncture region (1). In the majority of cases, the transition foci between metaplastic carcinoma and invasive ductal carcinoma were only observed following surgical biopsy (1,3,9,11). Therefore, extensive sampling by surgical biopsy and immunohistochemical examination should be performed to avoid misdiagnosis.…”
Section: Pathological Type Of Carcinoma Sonography ------------------mentioning
confidence: 99%
“…Therefore, traditional surgery is the preferred treatment choice (2). However, Song et al (3) identified that local tumor recurrence was common following a simple mastectomy; therefore, surgical techniques, including radical mastectomy and modified radical mastectomy, such as axillary dissection, may improve the prognosis and survival rate of a patient. Additionally, local and distant metastases are more frequent than other types of breast cancer during the follow-up subsequent to surgery (1).…”
Section: Pathological Type Of Carcinoma Sonography ------------------mentioning
confidence: 99%
See 3 more Smart Citations